Structural and functional characterization of HSP70 in the common bean (Phaseolus vulgaris) genome: An in sílico analysis (Research, Society and Development, 2023)
The common bean (Phaseolus vulgaris L.) is the most important legume worldwide, with global production estimated at 26.8 million metric tons in 2016, and is cultivated for its green pods as well as its dry seeds. Plants, in general, respond to environmental stresses with a series of physiological and molecular adaptation mechanisms. Heat shock proteins (HSPs) are protective proteins against a wide range of biotic and abiotic stress conditions and are highly conserved proteins that occur in all organisms in nature. HSP70 was first shown to be induced by high temperatures, but in recent years they have been considered as general stress-responsive proteins, which are induced by many abiotic stress conditions. Other studies have found that HSP70s are highly expressed under conditions of heat, cold and drought stress. Therefore, increased tolerance due to high expression of HSP70s has been demonstrated in some plant species. Several computational tools have been used for a broad analysis of the genome in silico and have been used to identify new proteins and genes. Although omics technologies have become significantly popular, there are few studies on the identification and characterization of HSP70 in Phaseolus vulgaris. Therefore, the objective of the present study was to carry out a structural characterization and identification of HSP70 in Phaseolus vulgaris using genome-wide computational methods, namely: phenetic analysis, allergenic potential analysis and three-dimensional modeling of the sequences.